The implication of full-day school: The role of self-determination in high school students' emotional well-being - Rahayu, Diah; Rifayanti, Rina; Ramadhani, Ayunda; Hardiansyah, Hardiansyah; Wardhana, Reishendra Arya; Awaliyah, Nur (Program Studi bimbingan Konseling PPs UNM Makassar, 2025)
This study examines the role of self-determination in relation to the emotional well-being of high school students attending full-day schools in Samarinda City. A quantitative approach with a correlational design was employed. Data were collected using self-determination and emotional well-being scales. The sampling technique used was cluster random sampling. The senior high schools that implemented the full-day school system in each sub-district in Samarinda City were grouped and allocated proportionally into eight representative schools, resulting in 359 student respondents. The results indicated a strong and significant relationship between self-determination and emotional well-being among high school students attending full-day schools in Samarinda City, as reflected by a correlation coefficient of r = 0.613. The role of self-determination contributed 37.6% to the score in emotional well-being. These findings suggest the need for further research to explore other factors influencing emotional well-being in full-day school students. Furthermore, schools are encouraged to implement programs that enhance student self-determination to support emotional well-being.